2006
DOI: 10.1213/01.ane.0000221186.64599.78
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Sulfate Attenuates Hemorrhagic Shock- Induced Hyperpermeability

Abstract: Morphine sulfate is often administered for patients requiring surgical intervention for the control of hemorrhage. Recent data implicate morphine as an immune modulator that affects white blood cells and increases infection rates. In addition, morphine releases histamine, an inflammatory mediator that increases microvascular permeability. Both of these actions of morphine could aggravate the inflammatory progress after hemorrhagic shock. In this study, we evaluated the role of morphine sulfate on microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Three 73-m 2 AOIs were assigned inside the venule, with three corresponding 73-m 2 areas just outside it. Leak was expressed as a ratio of fluorescence outside venules (AOIo) compared with that inside venules (AOIi), as previously described with slight modifications and after background subtraction (12): leak ratio ϭ (AOIo/AOIi) ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
“…Three 73-m 2 AOIs were assigned inside the venule, with three corresponding 73-m 2 areas just outside it. Leak was expressed as a ratio of fluorescence outside venules (AOIo) compared with that inside venules (AOIi), as previously described with slight modifications and after background subtraction (12): leak ratio ϭ (AOIo/AOIi) ϫ 100.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas a G(s) inhibitor or PKA inhibitor blocked only chronic effects, a PKC inhibitor blocked only acute effects (888). Morphine attenuated hemorrhagic shockinduced hyper permeability (182). Morphine and naloxone respectively decreased and increased the rate of hemorrhage-induced hypovolemia in sheep (363).…”
Section: B Cardioprotection and Ischemic Preconditioningmentioning
confidence: 97%
“…For the remaining studies (see Table, Supplemental Digital Content 6 for individual study details and results, http://links.lww.com/SHK/B319), data was too sparse to categorize the therapeutic agents based on their working mechanism. Charleston et al reported a reduction in hemorrhagic shock-induced microvascular leakage following treatment with morphine sulphate in the intestinal vascular bed (55). Inhibition of complement activation with C1-INH did not affect microvascular leakage (21), while targeting coagulopathy with rFXIII, a fibrin stabilizing factor, reduced pulmonary microvascular leakage (56).…”
Section: Others (N U 5)mentioning
confidence: 99%